Development of method of evaluation of concrete damage in the process of cyclic freeze-thawing; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Fursa T. V. Tatyana Viktorovna (2015, 2015)
Title screen